The Impact of Imports, Exports, Domestic Investment (PMDN), Regional Investment (PMDA), the Human Development Index (HDI), and Labor Productivity on Economic Growth in Indonesia (2019–2023) - Fasih Kalkun (Majapahit Journal of Islamic Finance and Management, 2025)
Economic growth is one of the key indicators for measuring a country's development success. This study aims to examine the impact of imports, exports, Domestic Direct Investment (DDI), Foreign Direct Investment (FDI), the Human Development Index (HDI), and labor productivity on economic growth in Indonesia during the 2019–2023 period. The urgency of this research lies in providing a deeper understanding of the factors influencing economic growth to support the formulation of more precise and effective policies.  This study employs a quantitative approach using panel data analysis from 34 provinces in Indonesia. The secondary data collected is processed using Eviews 10 software to identify significant relationships between variables. The findings indicate that exports, imports, HDI, and FDI have a significant influence on economic growth. In contrast, DDI and labor productivity do not show a significant impact on Indonesia’s economic growth.  The results of this study are expected to serve as a reference for policymakers and academics in designing more sustainable economic development strategies based on factors that have been empirically proven to contribute to national economic growth.